Impact of Forage Fertilization with Urea and Composted Cattle Manure on Soil Fertility in Sandy Soils of South-Central Vietnam - Keenan C. McRoberts; Quirine M. Ketterings; David Parsons; Tran Thanh Hai; Nguyen Hai Quan; Nguyen Xuan Ba; Charles F. Nicholson; Debbie J. R. Cherney (International Journal of Agronomy)
Increased production in smallholder beef systems requires improved forage management. Our objective was to evaluate the effects of composted cattle manure and mineral nitrogen (urea) application on soil fertility and partial nutrient balances in plots established to Brachiaria cv. Mulato II in south-central coastal Vietnam from 2010 to 2013. A randomized complete block design was implemented on six farms (blocks), with five rates of composted cattle manure (0, 4, 8, 12, and 24 Mg DM/ha per yr) and three urea rates (0, 60, and 120 kg N/ha per yr) in a factorial design. Soil was analyzed before and after the experiment. Compost increased soil pH, organic matter, Ca, Mg, and Mn. The effect of compost and urea applications on postexperiment soil fertility depended on preexperiment soil fertility for K, P, S, Mg, Zn, Mn, Cu, and organic matter, suggesting that the ability to maintain soil fertility depends on the interaction between soil organic and inorganic amendments and existing soil fertility. Highest farm yields were also achieved on farms with higher preexperiment soil fertility levels. Negative partial nutrient balances for N, P, and K suggest that yields will not be sustainable over time even for the highest fertilization inputs used in this experiment.